The structure of Mah Meri adjective phrases / Rabiatul Adawiyyah Abdullah - Rabiatul Adawiyyah , Abdullah (2016)
Recent developments of linguistic theory has provided the researcher with many concrete frameworks for an analysis of adjective phrases in the Mah Meri language, an Aslian Mon Khmer Austroasiatic language family. This research intends to provide an overview of the theoretical assumptions in the studies of adjective phrases and a summary of prior work on the endangered Aslian languages namely Mah Meri. In this dissertation, the morphosyntactic properties of Mah Meri language are described by adopting the framework by Thorne (1993) and Chomsky (1993). It demonstrates that the adjective has grades and occurs as pre- and post- nominal modifiers of a noun phrase and becomes predicative to any subject in a sentence. Adjective phrases can merge above and below the head of noun. The multiple adjectives orderings in Mah Meri is investigated by looking into framework by Quirk et al (1985) which is build up from the semantic groupings of adjectives by Dixon (2004). By adopting Minimalist Framework, the placement of noun and adjectives in a sentence is investigated to find out the nominal word order of Mah Meri which is based on the proposed nominal word order of the Southeast Asia. The Minimalist approach is adopted by the researcher as it provides a framework to develop a syntactic theory that uses a few basic principles as possible.